Wage Indexation And Political Cycles - Antonello Eugenio Scorcu (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1996)
If the wage indexation rate is chosen discretionarily, a Left hand government lowers it in order to increase the output effects of surprise inflation, while a Right hand government prefers high indexation. These choices magnify the differences between the inflation rates preferred by the two parties. When binding commitments before the signature of the labor contract are possible, both parties prefer a higher wage indexation with respect to the discretionary situation, in order to reduce the inflationary bias.
Keywords: 330